Estratégias de Ensino no Sistema Pré-escolar de Montenegro - Mićanović, Veselin; Novovic, Tatjana (Sensos-e, 2018)
Preschool education in Montenegro is undergoing a process of significant change, especially in the last two decades. The seriousness of this educational segment within the whole educational continuum corresponded with equally serious education policy solutions. The way of working with children of preschool age largely affects their development, level of autonomy and motivation for achieving educational goals through active learning and participation. When it comes to Montenegrin education system, this particular educational segment is becoming even more visible with the intention of faster, more comprehensive and effective development in perspective. Therefore, active learning through the process of a full children's participation and voluntary choice, is the basis of the leading preschool education paradigm in the contemporary educational context. Artigo Completo